Pathological bases of oxidative stress in the development of cardiovascular diseases - Costa, Mariane Róvero [UNESP]; Garcia, Jéssica Leite [UNESP]; De Almeida Silva, Carol Cristina Vágula [UNESP]; Ferraz, Ana Paula Costa Rodrigues [UNESP]; Francisqueti-Ferron, Fabiane Valentini [UNESP]; Artur Junio Togneri Ferron, [UNESP]; Corrêa, Camila Renata [UNESP] (Elsevier, 2020)
Cardiovascular disease is a term for disorders of the heart and blood vessels and its cause is multifactorial, involving behavioral, environmental, and genetic factors. All these causes can be associated with a phenomenon called oxidative stress. In this condition, oxidative stress occurs mainly due to the overproduction of reactive species that can damage macromolecules and can act as intracellular signaling. Several cellular compartments and systems are involved with the production of reactive species; however, mitochondria represent the largest source of reactive species in the cardiovascular system. The mechanisms by which oxidative stress can act, leading to the development of diseases, is still controversial. Thus this chapter aims to elucidate some of these mechanisms. We will present the conditions of ischemia and reperfusion, atherosclerosis, hyperlipidemia, inflammation, and peripheral arterial hypertension.
Keywords: Advanced glycation end-product (AGE); Cardiovascular disease; Mitochondrial dysfunction; Oxidative stress; Reactive species